Strategi Live Streaming dalam Membangun Engagement dan Kepercayaan Konsumen : Studi Kasus Pada Akun Tiktok Advan Indonesia - Rahmat Teguh Haryadi; Haryanto . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The rapid development of digital technology and social media in recent years has significantly transformed the business landscape, encouraging entrepreneurs to utilize live streaming as a highly interactive marketing strategy. This strategy serves not only as a promotional medium but is also crucial for enhancing consumer engagement and building consumer trust amidst fierce digital market competition. This study aims to conduct an in-depth analysis of the live streaming strategies implemented by businesses and to evaluate their simultaneous impact on the level of consumer engagement and trust formation. This research employs a descriptive qualitative approach with a case study design. The research population includes active social media users who have participated in live streaming commerce activities. A total of 15 informants were selected using a purposive sampling technique based on specific criteria: active social media usage, direct interaction experience during broadcasts, and prior purchase consideration. Data collection was conducted comprehensively through in-depth interviews, direct observations of live streaming sessions, and documentation of relevant digital content. Data analysis was carried out in three main stages: data reduction, data display, and conclusion drawing. The results indicate that interactive communication patterns, transparent product information delivery, and quick responses from the host significantly increase consumer engagement and trust. Furthermore, live product demonstrations and the presence of audience testimonials in the comment section proved effective in strengthening consumers' positive perceptions. In conclusion, effectively designed live streaming strategies can strengthen long-term relationships with consumers and support purchasing decisions within the digital marketing ecosystem.